2016
DOI: 10.1194/jlr.m062539
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL signals through Rho-GTPase to induce endothelial cell stiffening and promote capillary formation

Abstract: Oxidative modifications of LDL are a major risk factor in the development of vascular disease and are known to induce endothelial dysfunction, one of the earliest manifestations of atherosclerosis (1, 2). Our studies focus on the oxidized LDL (oxLDL)-induced impact on endothelial biomechanics and its role in vascular dysfunction.Our recent studies showed that the stiffness of aortic endothelial cells (ECs) is significantly increased by exposing the cells to oxLDL in vitro or by dyslipidemia in the dietinduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 48 publications
6
67
0
Order By: Relevance
“…Recently, it was shown that endothelial cell stiffness per se plays a role in adhesion and transmigration of immune cells (84,85). Our previous studies also demonstrate that an increase in endothelial cell stiffness and force generation enhances endothelial angiogenic potential in 3D cultures in vitro (10,11) and in matrigels inserted in vivo (56). Most recently, Busik et al demonstrated that a decrease in membrane fluidity, which is expected to reflect a decrease in lipid order, correlates with migration and homing of bone-marrow-derived circulating stem cells (86).…”
Section: Impact Of Oxidized Lipids On Endothelial Membrane Lipid Packmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, it was shown that endothelial cell stiffness per se plays a role in adhesion and transmigration of immune cells (84,85). Our previous studies also demonstrate that an increase in endothelial cell stiffness and force generation enhances endothelial angiogenic potential in 3D cultures in vitro (10,11) and in matrigels inserted in vivo (56). Most recently, Busik et al demonstrated that a decrease in membrane fluidity, which is expected to reflect a decrease in lipid order, correlates with migration and homing of bone-marrow-derived circulating stem cells (86).…”
Section: Impact Of Oxidized Lipids On Endothelial Membrane Lipid Packmentioning
confidence: 79%
“…Moreover, our studies further demonstrate that exposure to oxLDL induces an increase in F-actin stress fibers (80) and that endothelial stiffening induced by cholesterol depletion critically depends on the integrity of F-actin (6). In terms of the mechanism that links insertion of oxidized lipids to endothelial cell stiffening, our recent study demonstrates that for oxLDL and oxysterols, stiffening is mediated by the activation of the RhoA/Rock/PLCP/MLC2 pathway (56). oxPAPCs, however, were shown to activate two other members of the Rho-GTPase family, Rac1 and CDC42, while attenuating thrombin-induced RhoA activation (18,82).…”
Section: Impact Of Oxidized Lipids On Endothelial Membrane Lipid Packmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, in addition to oxidized fatty acyls, oxysterols play important roles in macrophage and EC biology [70, 71] (Box 1). As the esterified oxidized PUFA decompose to produce so-called oxidation end products, namely, short carbon chain aldehydes and ketones, they become uniformly proinflammatory.…”
Section: Inflammatory Effects Of Lipid Oxidation End Productsmentioning
confidence: 99%
“…Oxysterols, found both intracellularly and in OxLDL, induce a large number of profound cellular responses. For example, 7-ketocholesterol, a product of ROS-mediated cholesterol oxidation in OxLDL, regulates endothelial biomechanics and induces expression of inflammatory genes [70, 71]; enzymatically produced 25-hydroxycholesterol (25-OHC), among other oxysterols, activates the anti-inflammatory liver X receptor and other nuclear receptors and regulates function of insulin-induced gene 1. As is the case with oxidized PUFA products, oxysterols mediate both pro- and anti- inflammatory responses.…”
Section: Inflammatory Effects Of Lipid Oxidation End Productsmentioning
confidence: 99%